The Evaluation of Undergraduate Economics Curriculum for Graduate Employability in Nigerian Universities. A Case Study of Economics Undergraduates of University of Lagos, Lagos, Nigeria - Kamoru Olanrewaju Sheidu; Raphael John (Interdisciplinary Journal Of Lifelong Learning, 2025)
The study examined ‘’the evaluation of undergraduate economics curriculum for graduate employability in Nigerian Universities, a case study of economics undergraduate students in University of Lagos’’ The theory that suits this study is the ‘DOTS’ theoretical model which was advanced by Law and Watts. Descriptive survey design was adopted, and 137 copies of a questionnaire were administered to economics undergraduates at Lagos State University. Two research questions and hypotheses were formulated and tested using correlation statistical tool of analysis. The sample size for this study was two hundred participants comprising both male and female economics undergraduates selected randomly. The research instrument used for data collection was researcher-designed questionnaire; Pearson Product Moment Correlation Coefficient was used to test the research hypotheses at 0.05 level of significant.  The finding shows that there is a significant correlation between the skills in the job advertisements with those in the undergraduate economics curriculum. Also, there is significant relationship between skills acquired in econometrics and graduate employability. It was consequently recommended that Curriculum department should ensure that the need of employers of labour is captured when designing and developing the curriculum. NUC should ensure that the department of economics in various universities has a functional econometrics laboratory. Hence, lecturers should be sponsored for training so as to be equipped with a better approach of teaching the subject matter and undergraduate students should be encouraged on the benefits of gaining expertise in econometrics.